2014
DOI: 10.1186/1756-0500-7-544
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with genital human papillomavirus infection among adult females in the United States, NHANES 2007–2010

Abstract: BackgroundPatients with human papillomavirus (HPV) infection are at risk of developing cancer later in their life. Current research estimates the prevalence of genital HPV infection and explores the factors that are associated with the infection.FindingsThe National Health and Nutrition Examination Survey 2007–2010 was used in this research study. The study population included females in the United States aged 18–59 years. The weighted prevalence of HPV infection was 41.9%. An estimated 59.4% of non-Hispanic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 20 publications
8
37
4
1
Order By: Relevance
“…Similarly to previous studies, 9,14,18,24,26,27 our study found that sexual factors-for example, the number of lifetime sexual partners and the number of sexual partners within the past year-have a strong influence on anogenital HPV prevalence in both sexes. Notably, we found that participants who had ever used a towel supplied by a hotel had a higher HPV prevalence at external genital and PA sites, whereas hotel towel usage was not associated with vaginal HPV detection.…”
Section: Infectious Causes Of Cancersupporting
confidence: 88%
“…Similarly to previous studies, 9,14,18,24,26,27 our study found that sexual factors-for example, the number of lifetime sexual partners and the number of sexual partners within the past year-have a strong influence on anogenital HPV prevalence in both sexes. Notably, we found that participants who had ever used a towel supplied by a hotel had a higher HPV prevalence at external genital and PA sites, whereas hotel towel usage was not associated with vaginal HPV detection.…”
Section: Infectious Causes Of Cancersupporting
confidence: 88%
“…The US National Health and Nutrition Examination Survey in 2007-2010 on women aged 18-59 years revealed a 41.9% prevalence of genital HPV infection [97]. Multivariate analysis in this cohort revealed that HPV infection was related to age, number of sexual partners, smoking, educational level, income, and insurance status [97]. Similar results on the risk of persistent HPV infection have been confirmed in other studies [98,99].…”
Section: Discussionsupporting
confidence: 83%
“…To address this issue, the usefulness of self-sampling for HPV testing has been studied [95,96]. The US National Health and Nutrition Examination Survey in 2007-2010 on women aged 18-59 years revealed a 41.9% prevalence of genital HPV infection [97]. Multivariate analysis in this cohort revealed that HPV infection was related to age, number of sexual partners, smoking, educational level, income, and insurance status [97].…”
Section: Discussionmentioning
confidence: 99%
“…This finding mirrors those observed in other studies. 17, 26, 29, 30 We also found an association of ever having used a towel supplied by a hotel with oncogenic HPV infection in both sexes, which may provide new information for the secondary prevention of oncogenic HPV infection among women and men. No other questionnaire-based information, including age at first sexual intercourse, condom use or STDs, had a significant association with HPV infection.…”
Section: Discussionmentioning
confidence: 54%
“…Our finding that HPV 52, 58 and 16 were the most frequent oncogenic HPV types in women was concordant with the findings of previous studies in China and different from an American study (HPV 53, 16 and 51) and a meta-analysis of one million women on five continents (HPV 16, 18 and 52). 20, 23, 24, 25, 26, 27 In men, the three most common types were HPV 58, 52 and 39, which was different from other studies in Brazil (HPV 16, 66 and 59), Mexico (HPV 59, 51 and 16), the United States (HPV 16, 51 and 66), Anyang, China (HPV 16, 18 and 58), and on five continents (HPV 51, 16 and 56). 9, 16, 17 In both women and men, HPV 52 and 58 were the most prevalent types in our study, which further implies the necessity to vaccinate against HPV 52 and 58 in China.…”
Section: Discussionmentioning
confidence: 99%